2009
DOI: 10.3382/ps.2008-00478
|View full text |Cite
|
Sign up to set email alerts
|

Variability in bone mineralization among purebred lines of meat-type chickens

Abstract: The variability of bone traits was assessed in purebred lines of meat-type chickens using dual-energy x-ray absorptiometry. Experiment 1 evaluated changes in bone mineralization and size traits of the tibia and humerus in 4 purebred lines from 6 to 24 wk of age. Experiment 2 compared the same traits of the tibia, radius, and ulna of 9 purebred lines at 6 wk of age. Differences in bone traits among purebred lines were apparent in both experiments. Of the 4 purebred lines compared in experiment 1, line C demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Although tibia ash weight was not significantly different between T4 and T1, it was highest in T4 and lowest in T2 (P <0.05). This implies that the increase in dry bone weight and mineral content per unit bone length responds to mechanical forces placed on the bone (McDevitt et al, 2006;Whitehead, 2007;Talaty et al, 2009b). The weight of tibia ash has been found to be a more sensitive indicator of the amount of Ca and P in the diet (Hall et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although tibia ash weight was not significantly different between T4 and T1, it was highest in T4 and lowest in T2 (P <0.05). This implies that the increase in dry bone weight and mineral content per unit bone length responds to mechanical forces placed on the bone (McDevitt et al, 2006;Whitehead, 2007;Talaty et al, 2009b). The weight of tibia ash has been found to be a more sensitive indicator of the amount of Ca and P in the diet (Hall et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Skeletal integrity of broiler chickens has become a welfare and economic concern (Williams et al, 2004;Almeida Paz & Bruno, 2006;Fleming, 2008). Weak bones are an undesirable trait in growing broiler chickens, which has been linked to 1.1% mortality of birds, and an additional 2.1% condemnation or downgrading of carcasses during processing (Onyango et al, 2006;Talaty et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…These structural anomalies may contribute to increased mortality and morbidity that will reduce the overall well being of commercial meat genotypes. There are numerous factors that influence bone development, including nutrition, genetics, and management practices (Leeson, 1988;Bond et al, 1991;Edwards, 2000;Oviedo-Rondón et al, 2006;Talaty and Katanbaf, 2009). Examining the changes in bone characteristics and bone composition over time may help identify those ages or BW at which the potential for skeletal problems to occur is the greatest.…”
Section: Introductionmentioning
confidence: 99%
“…Jendral et al (2008) found that reduction of the physical exercise of hens led to loss of the bone weight and increased the tendency of bones to fractures. Talaty et al (2009aTalaty et al ( , 2009b confirmed the mineralisation changes of bones and the differences in the features of the skeleton between various lines of meat-type chickens. In turn, Williams et al (2003) emphasised that the growth rate of bones is strictly associated with their mineral content and density.…”
Section: Resultsmentioning
confidence: 55%